Gravitational search algorithm-based photovoltaic array reconfiguration for partial shading losses reduction - Hasanien, H.; Al-Durra, A.; Muyeen, S.M. (2016)
The operation of a photovoltaic (PV) array under partial shading (PS) conditions represents a great challenge in the PV systems. The PS of a PV array causes a reduction of the generated power of such array and increases the thermal losses inside the shaded modules. This paper presents the gravitational search algorithm (GSA) to optimally fully reconfigure the PV array with the purpose of reducing the PS losses. The single diode PV model is used to model the PV module. The GSA code is built using MATLAB environment. The target of the optimized problem is to minimize the irradiance level mismatch index. The reconfigurable PV array is modelled using MATLAB/SIMULINK environment. The validity of the GSA-based reconfigurable PV array is verified by the simulation results. The effectiveness of proposed PV array is evaluated by comparing its results with that of other PV array configurations under different PS and PV modules conditions.